(untitled) (Revista Electrónica Calidad en la Educación Superior, 2021)
The realization of this study was motivated by the people in charge of the chair of mathematics at the State Distance University (UNED), Costa Rica, who have expressed concerns regarding the production process and the software used for writing mathematical text in the teaching materials developed in the Didactic Written Material Production Program (PROMADE). The objective was to analyze the satisfaction of these people regarding the production process, to take concrete actions to improve it. The mixed methodology was used with a sequential exploratory design in this way: a semi-structured group interview made to the ten people in charge of the university’s chair of mathematics and the application of a questionnaire. In general, the participants were satisfied with the production process and, especially, with the work carried out by the academic producers (editors). Positive aspects and opportunities for improving PROMADE´s production process were identified, as well as others outside PROMADE, that negatively influence the motivation of the participants. Among the issues to be improved stand out the production time of the didactic units and the software used for writing the material. Based on the elements identified, specific actions were listed to solve the weaknesses and mitigate some of the aspects outside PROMADE that influence the motivation of the participants.